2016
DOI: 10.1080/13696998.2016.1188823
|View full text |Cite
|
Sign up to set email alerts
|

Cost of severe hypoglycaemia in nine European countries

Abstract: A common framework can be applied to estimate the economic burden of SHE in various countries, allowing one to identify the drivers of differences in cost. Treating DM is complex, and so no resolute conclusions ought to be drawn as to whether SHE management is better in one country than another.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
9

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
14
0
9
Order By: Relevance
“…The cost from the study in patients with T1DM is noticeably lower than that estimated in the present analysis (€808), which appears to be due to the fact that severe episodes were assumed to be treated by a family member in 75% of cases, compared with 33% in the present analysis. Another study that estimated the cost of severe hypoglycemia using experts’ opinions reported a cost per episode of just €172.33 [ 29 ] for all severe hypoglycemic episodes (not just insulin-related). However, there are a number of reasons for this difference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost from the study in patients with T1DM is noticeably lower than that estimated in the present analysis (€808), which appears to be due to the fact that severe episodes were assumed to be treated by a family member in 75% of cases, compared with 33% in the present analysis. Another study that estimated the cost of severe hypoglycemia using experts’ opinions reported a cost per episode of just €172.33 [ 29 ] for all severe hypoglycemic episodes (not just insulin-related). However, there are a number of reasons for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the two studies reporting a lower cost per severe hypoglycemic episode [ 14 , 29 ], a review article was also identified that reported the cost for a severe episode as €3597 and estimated the cost of a non-severe episode as between €30 and €35. These costs are both higher than the estimates in the present analysis, with the severe cost substantially so.…”
Section: Discussionmentioning
confidence: 99%
“…Another study assessed the total annual, direct, and indirect cost of SH events in nine European countries, including Spain. This study, conducted in 2016, reported an annual total cost for single SH event of €1076.05, €209.28 and €0.46 for hospital-treated, medical professional-treated and family-treated SH events in Spain, which in terms of the whole population affected translates into €32,339,530.58, €19,513,354.64 and €94,856.70, respectively [ 44 ]. Taking these figures into consideration, the prevention of hypoglycemia is essential in DM management programs given its impact on patients and on healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…This comprised £1.0 billion in direct costs, of which 71% was due to long-term complications, and £0.9 billion in productivity and social costs due to death, sickness, presenteeism and caregiver burden [11]. Hypoglycaemia is costly to treat [11][12][13][14][15]. The cost of a severe hypoglycaemic event treated in hospital in the UK for a person with T1DM was estimated to be £1034 in 2012 [15].…”
Section: 2mentioning
confidence: 99%